2016
DOI: 10.1007/s00705-016-2875-y
|View full text |Cite
|
Sign up to set email alerts
|

Paper-based archiving of biological samples from fish for detecting betanodavirus

Abstract: This study was carried out to evaluate the efficiency of the Flinders Technology Associates (FTA(®)) card (Whatman(®)) as a sampling device and storage platform for RNA from betanodavirus-infected biological samples (viz., larvae, broodstock, cell culture supernatants and rearing seawater spiked with infected materials). The study showed that FTA cards can be used to detect betanodaviruses by reverse transcription-polymerase chain reaction (RT-PCR). The diagnostic efficiency of RT-PCR from all sample types on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Plant samples were assessed in 31.9% of the included articles, and samples obtained from insects corresponded to 14.9%. These works aimed to amplify viral RNA of arboviruses that can cause disease in humans, and also viruses capable of causing disease in fishes and plants (Hall-Mendelin et al, 2010;Price et al, 2014;Flies et al, 2015;Yang et al, 2015;Navaneeth Krishnan et al, 2016;Hall-Mendelin et al, 2017;Melanson et al, 2017;Chikh-Ali et al, 2016). Viral specimens were derived from cell culture or from a commercial inactivated vaccine in 10.6% of the reports (Muthukrishnan et al, 2008;Li et al, 2012;Bankamp et al, 2013;Sakai et al, 2015;Montmayeur et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Plant samples were assessed in 31.9% of the included articles, and samples obtained from insects corresponded to 14.9%. These works aimed to amplify viral RNA of arboviruses that can cause disease in humans, and also viruses capable of causing disease in fishes and plants (Hall-Mendelin et al, 2010;Price et al, 2014;Flies et al, 2015;Yang et al, 2015;Navaneeth Krishnan et al, 2016;Hall-Mendelin et al, 2017;Melanson et al, 2017;Chikh-Ali et al, 2016). Viral specimens were derived from cell culture or from a commercial inactivated vaccine in 10.6% of the reports (Muthukrishnan et al, 2008;Li et al, 2012;Bankamp et al, 2013;Sakai et al, 2015;Montmayeur et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The cards can be kept at room temperature, eliminating the need for freezers, excessive storage space and transport of flammable liquids. FTA cards have been successfully used for the preservation of fish buccal cells and mucus, as a cheap alternative to freezing or commercial extraction kits 120,121 . Brown trout ( Salmo trutta ) and northern pike ( Esox Lucius ) DNA was successfully extracted noninvasively with no cross‐contamination from FTA cards 120 .…”
Section: Molecular Techniquesmentioning
confidence: 99%
“…Storage of parasite DNA on FTA cards has been successful, such as with samples containing parasites and parasite eggs 122,123 . DNA can be maintained on cards for years at room temperature and amplified following standard protocols, 124 but experimentally detectable viral RNA (Genus Betanodavirus ) decreased after 4 weeks even when cards were stored at 4°C 121 . A review of 47 studies indicated the maximum storage time for viral RNA on FTA cards ranged from 1 to 8 months at temperatures from −20°C to 37°C 125 .…”
Section: Molecular Techniquesmentioning
confidence: 99%
“…Both horizontal and vertical transmission has been demonstrated in various fish species [17]. Persistent or carrier infection may develop to an acute phase with biological and environmental stress factors and facilitate the vertical or horizontal transmission of the nodavirus [18].…”
Section: Nervous Necrosis Virusmentioning
confidence: 99%